Principles of good practice for concept definition in the context of translation and linguistic validation of clinical outcome assessments (COAs) - Benjamin Arnold; Dana Weiss; Emily Parks-Vernizzi; Barbara Brandt; Ana Popielnicki; Beatrice Tedeschi; Clayon Hamilton; Mark Wade; John Chaplin; Holger Muehlan; Jussi P. Repo; Sonya Eremenco (Journal of Patient-Reported Outcomes)
Abstract Background Translation teams conducting translation and cultural adaptation find it paramount to properly describe concepts of items within clinical outcome assessments (COAs). To minimize potential threats to linguistic/conceptual equivalence, these teams must understand the concepts a COA intends to measure. This research provides recommendations for the process of developing concept definitions in general, as well as specific recommendations on who should be involved in the process and what a concept definition document should contain. Methods The Concept Definition Working Group of the International Society for Quality of Life Research (ISOQOL) Translation and Cultural Adaptation Special Interest Group (TCA-SIG) carried out a literature review and a survey of 20 professionals working in the area of translation and linguistic validation of COAs. The Working Group based recommendations on a combination of survey results and consensus building via online meetings. Results Translation teams should develop concept definitions during the preparation phase of the translation process, assuming they do not already exist, and include COA developers and project managers with experience in linguistic validation and conceptual analysis of COAs. The Working Group recommends that concept definitions consist of information related to the therapeutic area being studied, information related to the COA development process, definitions of concepts and domains, as well as elaboration of colloquialisms and acceptable/unacceptable translation alternatives. We recommend centralized distribution of concept definitions. Conclusions Concept definitions guide stakeholders and ensure all parties align on the intended meaning of items being translated. While experts have made recommendations for best practices around translation and linguistic validation methodology, they have not clearly delineated the process of defining concepts. The Concept Definition Working Group of the ISOQOL TCA-SIG has therefore developed a set of recommendations for the process of defining concepts. With these recommendations the Working Group intends to standardize the development of concept definitions with the goal of enhancing conceptual equivalence across translations to support data pooling and provide confidence that clinical trial data are comparable, interpretable, and can be relied upon in evaluating clinical benefit of treatments.